Numerical Modeling of Composite Load-Induced Seabed Response around a Suction Anchor - Jingyao Ma; Hongyi Zhao; Dong-Sheng Jeng (Journal of Marine Science and Engineering, 2024)
Suction anchors play a crucial role as marine supporting infrastructure within mooring systems. In engineering practice, the composite load comprising nonlinear waves and cyclic pull-out loads can have adverse effects on the seabed soil, posing a threat to the pull-out bearing capacity of the suction anchor. While existing research predominantly focuses on cyclic pull-out loads, the influence of nonlinear wave actions at the seabed surface remains overlooked. This study employs a two-dimensional integrated numerical model to investigate the dynamic soil response around a suction anchor under the influence of both nonlinear waves and cyclic pull-out loads, focusing on the mechanisms that lead to liquefaction and the deterioration of the interfacial friction due to the excess pore pressure buildup. The numerical results reveal that the cyclic pull-out load is the primary factor in the deterioration of the frictional resistance at the suction–soil interface, especially when the pull-out load is inclined with the suction anchor. Parametric studies indicate that the relative difference in frictional resistance deterioration between cases considering and excluding surface water waves becomes more pronounced in soils characterized by a small consolidation coefficient (<semantics>Cv</semantics>) and relative density (<semantics>Dr</semantics>).